2020
DOI: 10.18311/ijmds/2020/24452
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Improves the Ultrastructure of Submandibular Salivary Glands of Streptozotocin Induced Diabetic Rats - A Qualitative Study

Abstract: Diabetes has well known damaging effects on different tissues of the body including salivary glands. Epidermal Growth Factor (EGF) facilitates healing and repair through different mechanisms including the increase in the activation and proliferation of fibroblasts. The aim of this study was to investigate if the effect of EGF was enough to repair the damage caused by diabetes in streptozotocin induced diabetic rats. Sixty adult male albino rats were divided into three groups. A control group, a streptozotocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
3
3
0
Order By: Relevance
“…This is in agreement with previous studies in the literature that investigated the effects of EGF on different tissues in diabetic patients [38], [39], [40], [41], [42], [43]. In addition to the above, previous studies using the same experimental rat animal model revealed results that are consistent with the present study [44], [45]. EGF restored normal cytokeratin expression [44] and the ultrastructural picture of submandibular salivary glands in diabetic rats [45].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous studies in the literature that investigated the effects of EGF on different tissues in diabetic patients [38], [39], [40], [41], [42], [43]. In addition to the above, previous studies using the same experimental rat animal model revealed results that are consistent with the present study [44], [45]. EGF restored normal cytokeratin expression [44] and the ultrastructural picture of submandibular salivary glands in diabetic rats [45].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the above, previous studies using the same experimental rat animal model revealed results that are consistent with the present study [44], [45]. EGF restored normal cytokeratin expression [44] and the ultrastructural picture of submandibular salivary glands in diabetic rats [45]. The consistency in results validates the use of our diabetes-EGF experimental rat model in future studies involving other oral tissues as well as different body organs.…”
Section: Discussionsupporting
confidence: 92%
“…This osmotic effect initiates degradation of large macromolecules within the injured cell and leads to the presence of cytoplasmic vacuoles. Furthermore, other cytoplasmic vacuolations might be due to degeneration of other cell organelles such as Golgi apparatus which appear as empty spaces ( Ankily et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The healing potential of EGF was documented in several studies. It was prevalent in epithelial cell re-epithelialization, proliferation, migration and renewal of gastric glands during renal epithelium regeneration ( Flaquer et al ., 2010 ), gastric ulcer healing ( Tarnawski & Ahluwalia, 2012 ), corneal epithelium ( Jeon et al ., 2018 ) and salivary glands ( Al-Ankily et al ., 2018 ; Shamel et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This profusion causes an osmotic effect that induces the breakdown of the macromolecules found in the injured cell and the presence of the vacuoles. Moreover, the intracytoplasmic vacuolations have also been explained by the deterioration of other cell organelles, especially the Golgi apparatus, whereby if acquiring a fatty nature, they appear as vacuoles [ 58 ]. In addition, the cell vacuoles may be due to reduced secretory activity of the acinar cells and a decrease in the secretory material of the granules [ 59 ].…”
Section: Discussionmentioning
confidence: 99%